Endodontic treatments on permanent teeth in pediatric patients aged 6–12 years old - Su-Min Lee; Ya-Hsin Yu; Bekir Karabucak (Journal of Dental Sciences, 2023)
Backgroud/purpose: The prevalence of carious lesions and traumatic injury in individuals between ages 6 and 12 is high. This study aimed to characterize pediatric patients aged 6–12 treated in the endodontic clinic and investigate the prevalence and patterns of their provided endodontic treatments. Materials and methods: Clinical and radiographic records of patients (ages 6–12) referred to the postgraduate Endodontics clinic from June 2017 to June 2020 were reviewed. Demographics, pre-and post-operative conditions, type of endodontic treatment, and behavioral management were collected. Results: A total of 6350 teeth from 6089 patients were treated in this period, and 425 teeth (6.7%) from 405 patients were included. Ages 9–11 were the most commonly treated age group. Significantly more lower molars (41.9%) and upper anterior teeth (36.7%) were treated (P < 0.05). The majority of teeth were diagnosed with pulp necrosis (39.5%), and the most common periapical diagnosis was normal apical tissues (39.8%), then symptomatic apical periodontitis (38.8%). The most common etiological factor was caries (63.5%). Two hundred six teeth (48.5%) were treated with root canal therapy, 161 teeth (37.9%) with vital pulp therapy, 46 teeth (10.8%) with apexification or regenerative endodontic procedure, 12 teeth (2.8%) with non-surgical retreatment. A statistically high number of patients (87.8%) tolerated the endodontic procedures without any sedation (P < 0.0001). Conclusion: Pediatric patients aged 6–12 compose around 7% of the population treated at the postgraduate Endodontics clinic, reflecting the high demand for endodontic treatment in a pediatric mixed dentition population.